Get live Maths 1-on-1 Classs - Class 6 to 12

Ex 9.4

Ex 9.4, 1 (i)

Ex 9.4, 1 (ii)

Ex 9.4, 1 (iii) Important

Ex 9.4, 1 (iv)

Ex 9.4, 1 (v) Important

Ex 9.4, 1 (vi) Important

Ex 9.4, 2 (i)

Ex 9.4, 2 (ii) Important

Ex 9.4, 2 (iii)

Ex 9.4, 2 (iv) Important

Ex 9.4, 3 (i)

Ex 9.4, 3 (ii) You are here

Ex 9.4, 3 (iii) Important

Ex 9.4, 3 (iv)

Ex 9.4, 3 (v) Important

Ex 9.4, 3 (vi)

Ex 9.4, 3 (vii) Important

Ex 9.4, 3 (viii)

Last updated at March 23, 2023 by Teachoo

Ex 9.4, 3 Simplify. (ii) (𝑎^2+5) (𝑏^3+3)+5 Here, there are 2 expressions: 1st expression = (𝑎^2+5) (𝑏^3+3) 2nd expression = 5 Solving 1st expression (𝑎^2+5) (𝑏^3+3) = 𝑎^2 (𝑏^3+3)+5(𝑏^3+3) = (𝑎^2×𝑏^3 )+(𝑎^2×3)+(5×𝑏^3 )+(5×3) = 𝑎^2 𝑏^3+3𝑎^2+5𝑏^3+15 Now, our expression is (𝑎^2+5) (𝑏^3+3)+5 = 𝑎^2 𝑏^3+3𝑎^2+5𝑏^3+15+5 = 𝒂^𝟐 𝒃^𝟑+𝟑𝒂^𝟐+𝟓𝒃^𝟑+𝟐𝟎